Implementation of Differentiated Learning Management in Indonesian Junior High School Education - Septrina, Eka; Hermita, Neni; Erlisnawati`, Erlisnawati (Program Studi Pendidikan Guru Sekolah Dasar, FKIP, Universitas Riau, 2024)
This study aims to analyze the implementation of differentiated learning management at SMP Negeri 42 Pekanbaru in the context of the Kurikulum Merdeka. This curriculum was launched to address the